International Management - Mead, Richard (Wiley, 2012)
This new edition of International Management secures the position of this successful text as the most comprehensive introduction to global cross-cultural management available. For the Fourth Edition, the text has been extensively revised and updated, with the addition of more student exercises, assignments, exam questions, and new material on the Middle East. As in previous editions of this popular text, students will find an invaluable guide to key management theories, linked to practical examples from the US, Europe, Asia, and, in this edition, from other regions.